Biobanking for tropical health: leveraging collaborative initiatives in the Lusophone world - Arez, Ana Paula; Souto, Aline; da Silva, Manuela; do Nascimento, Carlos Roberto Sobrinho; Couto, Isabel; Belo, Silvana; Lima, Nelson (Frontiers in Tropical Diseases, 2024)
Biological collections and biobanks are essential for scientific research and innovation, supporting various scientific fields such as health sciences, biotechnology, food and agriculture. They preserve and provide diverse organisms, biological materials and their associated data, enabling the study of biodiversity, diseases, and their evolution and ecological functions. These collections are crucial for addressing global challenges like biodiversity loss, sustainable food and feed production, and human health, including understanding variations in pathogenic and etiologic agents over time. Biobanks support the development of new therapies, biomarkers, and diagnostic tests while promoting equitable benefit sharing from genetic resource utilization and developing and implementing international standards, crucial for improving research reliability and reproducibility. Collaborative networks enhance biobank operation by organizing data, exchanging biological material and facilitating trans-biobank studies and protocols standardization/harmonization. The establishment of the Lusophone Network of Biobanks and Biological Collections is a significant step toward promoting collaboration, capacity building and capacity development among Portuguese-speaking countries, many of them dealing with tropical health issues, facilitating knowledge exchange and resource sharing for scientific advancement on a global scale.